Những câu hỏi liên quan
MD
Xem chi tiết
MD
Xem chi tiết
MD
Xem chi tiết
MD
Xem chi tiết
MD
Xem chi tiết
H24
Xem chi tiết
MD
Xem chi tiết
MD
Xem chi tiết
H24
Xem chi tiết
KR
25 tháng 6 2023 lúc 21:21

`@` `\text {Ans}`

`\downarrow`

`1,`

\((y-5)(y+8)-(y+4)(y-1)\)

`= y(y+8) - 5(y+8) - [y(y-1) + 4(y-1)]`

`= y^2+8y - 5y - 40 - (y^2-y + 4y - 4)`

`= y^2+8y-5y-40 - y^2+y-4y+4`

`= (y^2-y^2)+(8y-5y+y-4y) +(-40+4)`

`= -36`

Vậy, bt trên không phụ thuộc vào gtr của biến.

`2,`

\(y^4-(y^2+1)(y^2-1)\)

`= y^4 - [y^2(y^2-1)+y^2-1]`

`= y^4- (y^4-y^2 + y^2-1)`

`= y^4-(y^4-1)`

`= y^4-y^4+1`

`= 1`

Vậy, bt trên không phụ thuộc vào gtr của biến.

`3,`

\(x(y-z) + y(z-x) +z(x-y)\)

`= xy-xz + yz - yx + zx-zy`

`= (xy-yx) + (-xz+zx) + (yz-zy)`

`= 0`

Vậy, bt trên không phụ thuộc vào gtr của biến.

`4,`

\(x(y+z-yz) -y(z+x-xz)+z(y-x)\)

`= xy+xz-xyz - yz - yx + yxz + zy - zx`

`= (xy-yx)+(xz-zx)+(-xyz+yxz)+(-yz+zy)`

`= 0`

Vậy, bt trên không phụ thuộc vào gtr của biến.

`5,`

\(x(2x+1)-x^2(x+2)+x^3-x+3\)

`= 2x^2+x - x^3 - 2x^2 + x^3 - x + 3`

`= (2x^2-2x^2)+(-x^3+x^3)+(x-x)+3`

`= 3`

Vậy, bt trên không phụ thuộc vào gtr của biến.

`6,`

\(x(3x-x+5)-(2x^3+3x-16)-x(x^2-x+2)\)

`= 3x^2 - x^2 + 5x - 2x^3 - 3x + 16 - x^3 + x^2 - 2x`

`= -3x^3 + 3x^2 + 16`

Bạn xem lại đề bài.

`\text {#KaizuulvG}`

Bình luận (0)